2021
DOI: 10.1007/s00261-021-03225-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chronic liver disease by multiparametric ultrasound: results from a private practice outpatient facility

Abstract: Purpose To assess chronic liver disease (CLD) using multiparametric US in a private practice setting in a cohort of patients with increased skin-to-liver distance. Methods 110 consecutive patients with increased skin-to-liver distance scheduled for US assessment of CLD were reviewed for study completion time, liver stiffness values (LS), attenuation imaging, and shear wave dispersion slope. The ROI was placed 2 cm below the liver capsule. The study included patients with NAFLD/NASH (68), hepatitis C (30), prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Although a 25-mm SCD cut-off has been used in a prior publication, 13 this is not validated as yet. 32 The current study population with a typical tertiary centre pattern of referral has an expected wide range of indications. There was a significant, though, weak positive correlation between HRI and ATI, and between HRI SG and ATI SG, in the total population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a 25-mm SCD cut-off has been used in a prior publication, 13 this is not validated as yet. 32 The current study population with a typical tertiary centre pattern of referral has an expected wide range of indications. There was a significant, though, weak positive correlation between HRI and ATI, and between HRI SG and ATI SG, in the total population.…”
Section: Discussionmentioning
confidence: 99%
“…However, in obese patients (defined as BMI >25 kg/m 2 ) the area under the receiver operating characteristic curve for steatosis diagnosis was quoted as ‘…>0.7 in obese patients, corresponding to moderate diagnostic value…’. Although a 25‐mm SCD cut‐off has been used in a prior publication, 13 this is not validated as yet 32 …”
Section: Discussionmentioning
confidence: 99%
“…Ferraioli et al 20 mentioned that an imaging protocol for attenuation imaging (ATI) that consists of 5 consecutive measurements lasts approximately 1 minute. A recent study conducted by Aitharaju et al 21 revealed that multiparametric ultrasound examinations which included a different vendor‐specific liver fat quantification tool (Attenuation imaging, ATI, Canon) can be performed in a short time period (mean time period for the exam was 129.7 ± 62.1 seconds). Furthermore, they reported that the difference in the examination time between the more experienced and less experienced sonographers was statistically significant 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the energy loss while taking the frequency into account can quantify the liver fat content. There are different approaches used to estimate attenuation, which is described elsewhere 12–14 …”
mentioning
confidence: 99%
“…There are different approaches used to estimate attenuation, which is described elsewhere. [12][13][14] To improve the clinical use of attenuation imaging, various US vendor systems should provide similar attenuation coefficients (AC) and have similar cut-off values. In this paper, we compare the attenuation coefficient estimate for liver fat fraction from 2 different US systems, one of which has pre-released software.…”
mentioning
confidence: 99%